Nutrient Management Programs, Nitrogen Fertilizer Practices, and Groundwater Quality in Nebraska’s Central Platte Valley (U.S.), 1989–1998 - Stan Daberkow; Harold Taylor; Noel Gollehon; Milt Moravek (The Scientific World Journal)
Given the societal concern about groundwater pollution from agricultural sources, public programs have been proposed or implemented to change farmer behavior with respect to nutrient use and management. However, few of these programs designed to change farmer behavior have been evaluated due to the lack of detailed data over an appropriate time frame. The Central Platte Natural Resources District (CPNRD) in Nebraska has identified an intensively cultivated, irrigated area with average groundwater nitrate-nitrogen (N) levels about double the EPA’s safe drinking water standard. The CPNRD implemented a joint education and regulatory N management program in the mid-1980s to reduce groundwater N. This analysis reports N use and management, yield, and groundwater nitrate trends in the CPNRD for nearly 3000 continuous-corn fields from 1989 to 1998, where producers faced limits on the timing of N fertilizer application but no limits on amounts. Groundwater nitrate levels showed modest improvement over the 10 years of this analysis, falling from the 1989–1993 average of 18.9 to 18.1 mg/l during 1994–1998. The availability of N in excess of crop needs was clearly documented by the CPNRD data and was related to optimistic yield goals, irrigation water use above expected levels, and lack of adherence to commercial fertilizer application guidelines. Over the 10-year period of this analysis, producers reported harvesting an annual average of 9729 kg/ha, 1569 kg/ha (14%) below the average yield goal. During 19891998, producers reported annually applying an average of 162.5 kg/ha of commercial N fertilizer, 15.7 kg/ha (10%) above the guideline level. Including the N contribution from irrigation water, the potential N contribution to the environment (total N available less estimated crop use) was estimated at 71.7 kg/ha. This is an estimate of the nitrates available for denitrification, volatilization, runoff, future soil N, and leaching to groundwater. On average, between 1989–1993 and 1994–1998, producers more closely followed CPNRD N fertilizer recommendations and increased their use of postemerge N applications an indication of improved synchrony between N availability and crop uptake.